Análisis de Factibilidad para la Implementación de una Aplicación Móvil que Permita Localizar las Aulas de Clases y Unidades Academicas en la UTB. - Duque Gaibor, Luis Carlos (2018)
The Technical University of Babahoyo with the day to day has had problems with the newly admitted students as well as with the regular students regarding the location of their academic units, classrooms and departments for which students to achieve a location within the perimeter of the university in a faster way, they would have as option a location application through the wireless connection through a smart mobile device with Android operating system. The main reason for the implementation of this type of mobile application is due to the disorientation that students have when wanting to go to a specific academic point. What we mean by disorientation is the way to get lost or lost from a person. In such a way that to get the mobile application to have a development, we will use the requirements engineering phase, at the same time we must start with the feasibility study or feasibility study. The conclusions reached from the feasibility study should generate a report that will show us whether the requirements engineering is feasible or not to continue with the development of the system. The main peculiarity that we will observe of this initiative is the benefit that will be had when implementing a mobile application of location which will satisfy the needs of the students of the Technical University of Babahoyo to avoid getting lost when wanting to reach an academic unit either by the delivery of a special document, as well as avoid losing activities in the classrooms of any career.